2021
DOI: 10.3390/molecules26247579
|View full text |Cite
|
Sign up to set email alerts
|

Yukmijihwang-Tang Suppresses Receptor Activator of Nuclear Factor Kappa-B Ligand (RANKL)-Induced Osteoclast Differentiation and Prevents Ovariectomy (OVX)-Mediated Bone Loss

Abstract: Yukmijihwang-tang (YJ) has been used to treat diabetes mellitus, renal disorders, and cognitive impairment in traditional medicine. This study aimed to evaluate the anti-osteoporotic effect of YJ on ovariectomy (OVX)-induced bone loss in a rat and receptor activator of nuclear factor kappa-B ligand (RANKL)-mediated osteoclast differentiation in bone marrow macrophages (BMMs). YJ reduced the formation of tartrate-resistant acid phosphatase (TRAP)-positive multinucleated cells (MNCs) in an osteoclast/osteoblast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Rehmanniae Radix Praeparata is the main nourish kidney-yin component of the Yukmijihwang-Tang, which inhibited RANKL-induced OC differentiation, resorption and fusion and OC differentiation in the coculture system of bone marrow cells (BMCs) and OBs and BMMs and downregulated OC-related genes, which may be related to the inhibition of the p38, JNK, ERK, and NF-κB signalling pathways. Han and Kim, (2021) ; Shim et al (2011) Moreover, the study found that it upregulated the expression of the immune-related gene IRF1 in the JAK/STAT pathway in PMOP patients with kidney yin deficiency. Chen et al (2017) However, its mechanism has not been explored with regard to immune cells.…”
Section: Immunoregulation Mechanisms By Which Nourishing Kidney-yin H...mentioning
confidence: 95%
See 1 more Smart Citation
“…Rehmanniae Radix Praeparata is the main nourish kidney-yin component of the Yukmijihwang-Tang, which inhibited RANKL-induced OC differentiation, resorption and fusion and OC differentiation in the coculture system of bone marrow cells (BMCs) and OBs and BMMs and downregulated OC-related genes, which may be related to the inhibition of the p38, JNK, ERK, and NF-κB signalling pathways. Han and Kim, (2021) ; Shim et al (2011) Moreover, the study found that it upregulated the expression of the immune-related gene IRF1 in the JAK/STAT pathway in PMOP patients with kidney yin deficiency. Chen et al (2017) However, its mechanism has not been explored with regard to immune cells.…”
Section: Immunoregulation Mechanisms By Which Nourishing Kidney-yin H...mentioning
confidence: 95%
“…(Rehmanniae Radix Praeparata). Zhou and Tang, (2016) Chinese formulae ( Han and Kim 2021 ), botanical drugs ( Liu et al 2017 ), and natural products ( Wang et al 2018b ) used to tonify the kidney have been proven to regulate OCs and OBs and improve bone structure and function to prevent and treat immune-mediated bone diseases with high clinical effectiveness and safety. Kidney-tonifying Chinese herbs have a direct regulatory effect on OCs, but in recent years, based on the close relationship between OCs and the immune system, research into kidney-tonifying herbs controlling OCs via the immune system has gained attention.…”
Section: Introductionmentioning
confidence: 99%